Persaudaraan Dan Persahabatan Sosial Ensiklik Paus Fransiskus: Kontribusi Dialog Antar Agama Indonesia - Edison R.L. Tinambunan (Litbang STFT Widya Sasana Malang, 2022)
There have been many inter religion dialogues and researches made recently. Every research has its own specialty to support the dialogue. Pope Francis’ encyclical (All Brothers) – which discusses the issues of fraternity and social friendship - meets the inter-religion dialogue in Indonesia. This article tries to review the encyclical in its term to contribute to the dialogue. The research uses qualitative methods with an interpretation approach and synthetic study of the encyclical to convey that it has a great contribution to the inter-religion dialogue. The emphasis of the inter-religion dialogue in this encyclical begins with human nature that starts from and goes to humanity. This implies that human being involves fraternity and friendship. A dialogue should start from the same foundation of humanity and go to the unlimited fraternity and friendship which sees the religion differences, not as an obstacle but rather as a process of mutual understanding.